2019
DOI: 10.1097/md.0000000000015700
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of risk stratification protocols and clinical, physical, and biochemical parameters to previse signals and symptoms during cardiovascular rehabilitation programs

Abstract: Introduction Despite the benefits, cardiovascular rehabilitation programs (CRPs) have been related to the appearance of signals and symptoms. Risk stratification protocols are commonly used to identify risks during the physical exercise; however, studies that investigate their efficacy to previse signals and symptoms are inconclusive. Furthermore, clinical, physical, and biochemical parameters have been used as risk markers for the appearance of adverse events, and to investigate their efficacy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…1). 23 The program was carried out three times a week on alternate days (Mondays, Wednesdays and Fridays), and each session lasted 60 min. Figure 1 shows the sequence of the program and the moments when the monitoring was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 23 The program was carried out three times a week on alternate days (Mondays, Wednesdays and Fridays), and each session lasted 60 min. Figure 1 shows the sequence of the program and the moments when the monitoring was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the sequence of the program and the moments when the monitoring was carried out. More information is available on the full protocol of the study that this work belongs to 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants of this study were recommended to perform 60-minutes of supervised exercise 3 times per week. Each exercise session was divided into 4 phases: (1) initial rest, 5 minutes – aimed to assess the patients’ initial cardiorespiratory parameters and complications that occurred outside the rehabilitation environment; (2) warm-up, 15 minutes – patients perform progressive resistance exercise aimed to prepare their body for the next step progressively; (3) Aerobic exercise, 30 minutes – patients performed moderate aerobic exercise on a treadmill and/or bike, with exercise intensity prescribed individually and based on the heart rate reserve formula; 25 and (4) relaxation, 10 minutes – return the patient’s cardiorespiratory parameters to values close to the initial ones.…”
Section: Methodsmentioning
confidence: 99%
“…These complications were recorded per session and only one occurrence was considered if participants reported the same complication more than one time in the same session. More details regarding the cardiac rehabilitation program and simple complications data collection were already reported by Vanzella et al 25 Participants were also asked to reported any complications that occurred out of the cardiac rehabilitation environment. Those would be included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%